Fibrillar Amyloid Plaque Formation Precedes Microglial Activation - Jung, Christian K. E. (PLoS One, 2015)
In Alzheimer’s disease (AD), hallmark β-amyloid deposits are characterized by the presence of activated microglia around them. Despite an extensive characterization of the relation of amyloid plaques with microglia, little is known about the initiation of this interaction. In this study, the detailed investigation of very small plaques in brain slices in AD transgenic mice of the line APP-PS1(dE9) revealed different levels of microglia recruitment. Analysing plaques with a diameter of up to 10 μm we find that only the half are associated with clear morphologically activated microglia. Utilizing in vivo imaging of new appearing amyloid plaques in double-transgenic APP-PS1(dE9)xCX3CR1(+/-) mice further characterized the dynamic of morphological microglia activation. We observed no correlation of morphological microglia activation and plaque volume or plaque lifetime. Taken together, our results demonstrate a very prominent variation in size as well as in lifetime of new plaques relative to the state of microglia reaction. These observations might question the existing view that amyloid deposits by themselves are sufficient to attract and activate microglia in vivo.